Identification of Difficulty in Resolving Problem Trigonometric Functions Limit in Class XI MA PIP (Islamic Education Parigi) Central of Habirau - annor, Alfi (Jurnal PTK dan Pendidikan, 2016)
This research is a field (field research) the research done by going directly to the field to investigate and identify the difficulties in solving problems pertaining to matter limit trigonometric functions in class XI IPA at MA PIP (Islamic Education Parigi) Habirau Central , Researchers describe the forms of the mistakes made by the students as a sign of difficulty for students in solving the limit of trigonometric functions. Based on the analysis of data from the four aspects of student difficulties in solving the limit of trigonometric functions, difficulties in implementing aspects of the basic formula of limit of trigonometric functions have error rates of students reached 94.56%. While the difficulty in outlining aspects of a matter form has an error rate of 86.95%. As for the difficulties in implementing aspects of the main limit theorem has an error rate of 65.21% and the difficulties in aspects perform arithmetic operations / computing student has an error rate of 52.70%. From the analysis, it appears that the location of the difficulties highest / most numerous in aspects of applying the basic formula limit of trigonometric functions. Key word: math difficulties, problems limit function trigonemetri